Post Operative Chylothorax after Pediatric Cardiac Surgery - Hassan, MK; Hosain, SN; Hasan, KA; Ahsan, NAK; Chowdhury, MMG (Bangladesh Medical Journal, 2009)
We reviewed the management of 6 cases of chylothorax (5 male, 1 female; 1-12 years old) following 500 cardiothoracic procedures during January 2004- December 2006 at National Institute of Cardiovascular Diseases, Dhaka. Results: The surgical procedures preceding the occurrence of lymph leak included ligation of PDA in 3 patients (50%), modified Blalock-Taussig Shunt in 2 cases (33.33%), bidirectional Glenn shunt in 1 case (16.67%). A protocol for management of postoperative chylothorax was applied for all patients. In this protocol, non-surgical management was always the first line of treatment for patients with postoperative chylothorax in the form of intercostal tube drainage and diet modification using either medium-chain triglycerides (MCT). All of our patients responded to conservative therapy. Conclusions: Conservative management of postoperative chylothorax should be the first line of treatment in postoperative chylothorax either by MCT diet alone or (in case of failure) to be followed by TPN and complete bowel rest. DOI: 10.3329/bmj.v36i2.3610 Bangladesh Medical Journal 36(2) 2007 42-43